Prosthodontic rehabilitation of a patient with amelogenesis imperfecta - D R Prithviraj; Vishal Singh; Sarvanan Kumar; D P Shruti (Wolters Kluwer Medknow Publications, 2009)
Amelogenesis imperfecta has been described as a complex group of hereditary enamel defects that disturbs the enamel structure and exists independent of any related systemic disorder. A 24-year-old male patient presented with discolored and hypersensitive teeth. The aim of the treatment was to reduce dental hypersensitivity and restore esthetics and masticatory function. The maxillary and mandibular teeth were prepared and metal ceramic crowns were cemented on the prepared teeth. The final treatment result provided the patient with improved dental esthetics and functional efficiency that enhanced his self-image.